Grape Leaffolder, Desmia funeralis (Hübner) (Insecta: Lepidoptera: Pyraustidae) - Frank W. Mead; Susan E. Webb (EDIS, 2004)
The grape leaffolder is a common and widely distributed species that is a minor pest of grapes in the United States. In Florida the grape leaffolder has done substantial damage to grape leaves in September and October when growers have discontinued their spray programs after harvest. Excessive defoliation may deplete the food reserves in the vine sufficiently to reduce the size of the next crop. This document is EENY-192 (originally published as DPI Entomology Circular 87), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: February 2001.